The early church on killing : a comprehensive sourcebook on war, abortion, and capital punishment - Sider, Ronald J. (Grand Rapids, Mich. : Baker Academic, 2012)
"Noted theologian Ron Sider lets the testimony of the early church speak in the first of a three-volume series on biblical peacemaking. This volume offers a thorough, comprehensive treatment on topics of perennial concern--war, abortion, and capital punishment--providing English translations for all extant data directly relevant to the treatment of these issues by the early church until Constantine. Primarily, it draws data from early church writings, but other evidence, such as archaeological finds and Roman writings, is included. The book contains brief introductions to every Christian writer cited and explanatory notes on many specific texts. The Early Church on Killing will be a helpful text in courses on ethics, theology, and church history"--Publisher description.
Christian writers before Constantine. Didache -- The Epistle of Barnabas -- First Clement -- Second Clement -- Apocalypse of Peter -- Justin Martyr -- Tatian -- Irenaeus -- Athenagoras -- Clement of Alexandria -- Tertullian -- Minucius Felix -- Didascalia apostolorum -- Julius Africanus -- Origen -- Cyprian -- Gregory Thaumaturgus -- Dionysius of Alexandria -- Archelaus -- Adamantius, Dialogue on the true faith -- Arnobius of Sicca -- Lactantius -- Church orders and synods. Apostolic tradition -- Three later church orders -- Synod of Arles -- Miscellaneous items. The Infancy Gospel of Thomas -- Paul of Samosata -- The Acts of Xanthippe and Polyxena -- Other evidence of Christian soldiers before Constantine. "The Thundering Legion" -- A third-century Christian prayer hall near a military camp -- Epitaphs -- Military martyrs -- Eusebius's Ecclesiastical history -- An early Christian kingdom?
Includes bibliographical references (p. 197-202) and indexes.
Keywords: Death -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Murder -- Religious aspects -- Christianity; War -- Religious aspects -- Christianity; Abortion -- Religious aspects -- Christianity; Capital punishment -- Religious aspects -- Christianity